Nupela brevistriata sp. nov. – a new, terrestrial diatom species from Southeast Asia. Issue 4 (2nd October 2019) - Rybak, Mateusz; Solak, Cüneyt Nadir; Noga, Teresa; Glushchenko, Anton; Williams, David M.; Kulikovskiy, Maxim
Abstract : The genus Nupela Vyverman & Compère comprises 81 species, which have been reported from different continents. This study presents the morphological characteristics of Nupela brevistriata sp. nov. found in moss samples collected from soil and tree bark in Southeast Asia, on the islands of Palambak and Sumatra. Light and scanning electron microscope observations are presented and a formal description is offered for the new species. Nupela brevistriata sp. nov. is characterized by the valves having very short striae, capitate apices and a large central and axial area; it occurred rarely (<2%) in assemblages dominated by typically terrestrial species, such as members of Ferocia Van de Vijver & Houk, Angusticopula Houk, Klee & H. Tanaka, Luticola D.G. Mann, Humidophila Lowe et al. and Hantzschia Grunow.